The Advanced Medical Science and Technology: A Challenge to The Higher Education in Developing Countries - I.G.N. Gde Ranuh (Indonesian Pediatric Society, 1996)
Indonesia's second stage of the National Long-Term Development Plan is a determinant factor for the shape of the country by the year 2020. A new era of development in the next 25 years will be of an unprecedented magnitude and far reaching significance for the future of the country as well as for South East Asia. Health development as one of the essential components, will play a significant role as it is the foundation for the well-being of the society without which development and progress will not be accomplished. On the other hand, a promising health development will depend on the availability of the human resources with a proper scientific background in the field of medical sciences. Therefore, health research is an effective way to solve many health problems encountered in the country. This condition in turn depends on on the advancement of the higher education to participate in the development. The WHO strategy for UFA by the Year 2000 specifically states that health research and development policies are the essentia] components of national health. An effective mechanism, coordination of research activities, the use and dissemination of its results should be established. The unique situation in Indonesia is described, in regard to geographical position, multiethnic, sociocultural traditional beliefs, health situation and services available. Facing two patterns of diseases, the commonly established infectious diseases and the new emerging diseases as a consequence of industrialization, the access to the advanced medical science and technology that develop rapidly are the challenge to the higher education to solve those problems effectively and efficiently in the years to come.